Impact of the Stress Status of Employees on the Enterprise Technology Management Cost Through Matter-Element Analysis Under Psychological Health Education - Zhang, Ximeng; Han, Fanshen; Gao, Ming; Liu, Lu; Wang, Xiaping (Frontiers in Psychology, 2021)
In order to analyze the stress sources and stress-coping strategies of employees in construction enterprises, to explore the influencing factors of enterprise technical management cost, and to offer suggestions for employees' mental health education, in this study, 372 employees of Shandong Construction Engineering Group Co., Ltd were selected for a questionnaire survey. The influence of stress sources and stress-coping strategies in employees' mental health were compared, based on different demographic variables. An evaluation model of the factors affecting the technology management cost was constructed using matter-element analysis method, with the objective factors evaluated. The results showed that the stress value of work characteristics was the highest (4.26±0.511), followed by the organizational structure and atmosphere (4.15±0.382); stress-coping strategies at the individual level (1.84±0.315) scored higher than that at the organizational level (1.67±0.248) (P<0.05); notable differences were noted in balance between work and family between males and females (P<0.05); notable differences were noted in work characteristics, role orientation, personal relationship, and balance between work and family between subjects of different ages (P<0.05); notable differences were noted in work characteristics, and balance between work and family between the married and the unmarried (P<0.05); notable differences were noted in role stress and work characteristics between subjects in different positions (P<0.05); the major factors influencing enterprise technical management cost included price index, proportion of development cost, proportion of fixed investment, rate of power equipment, development of mechanical and artificial intelligence, proportion of labor cost, rate of technical equipment, output value, technical management informatization, and national policy. In conclusion, work characteristics, organizational structure and atmosphere were the two major sources of stress for employees in Shandong Construction Engineering Group Co., Ltd. Many employees coped with stress at the individual level, and enterprises needed to strengthen the psychological health education for employees at the organizational level. In practice, enterprises need to develop mechanical artificial intelligence, information technology management, and keep aligned with national policy.